Application Of Saving Matrix Method In Determining 3 Kg Lpg Distribution Routes To Minimize Transportation Costs In. Pojur Real Madura - Agung Firdausi Ahsan; Lukmandono (Universitas Muhammadiyah Sidoarjo, 2021)
The transport route is a solution that minimizes the cost of distribution. The savings matrix method is the vehicle routing problem (VRP) method for obtaining an efficient route. The use of this method is to combine the destination points with the greatest distance savings and to take into account the volume of demand per destination. Then order the visits to the vehicle so that an efficient delivery route is obtained. This paper discusses the use of the savings matrix method in the determination of product delivery routes for PT Pojur Real Madura. At the end of the work, it turned out that this method showed that the route obtained was less than the original route, namely from 16 routes to 10 routes. Within a month, distance savings of 184 km or about 30 per cent were achieved, fuel savings of 61 liters or about 26 per cent were achieved, so that the use of the vehicle was reduced, which meant that costs could be minimized.